Expression Regulation of Major Histocompatibility Complex Class I and Class II Encoding Genes - van den Elsen, Peter J. (Frontiers in Immunology, 2011)
MHC-I and MHC-II molecules play an essential role in the immune response to pathogens by virtue of their ability to present peptides to CD8+ and CD4+ T cells, respectively. Given this critical role, MHC-I and MHC-II genes are regulated in a tight fashion at the transcriptional level by a variety of transcription factors that interact with conserved cis-acting regulatory promoter elements. In addition to the activities of these regulatory factors, modification of chromatin also plays an essential role in the efficient transcription of these genes to meet with local requirement for an effective immune response. The focus of this review is on the transcription factors that interact with conserved cis-acting promoter elements and the epigenetic mechanisms that modulate induced and constitutive expression of these MHC genes.